2010
DOI: 10.1016/j.molcatb.2009.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of catechol-O-methyltransferase (COMT) by some plant-derived alkaloids and phenolics

Abstract: a b s t r a c tIn this study, as an alternative to the medicines, natural compounds extracted from plant species (Peganum harmala, Cistus parviflorus and Vitex agnus-cactus) were investigated in order to inhibit the catechol-O-metyhltranferase (COMT) activity. In fluorometric enzyme assay, S-adenosylmethionine (SAM) and aesculetin (ES) were used as methyl donor and acceptor substrates, respectively. Their K m values were determined as 3.5 ± 0.3 M and 6.4 ± 0.4 M in absence of inhibitor. Inhibition performances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It was shown in another in vitro study that the extract of P. harmala has the ability to inhibit catechol-O-methyltransferase and thereby the methylation of catecholamines with a mixed type mechanism. [ 34 ] All of these effects represent an idea that P. harmala and its derivatives could be used for treatment of mood disorders and are potent alternatives for current anti-depression drugs.…”
Section: Effects On Nervous Systemmentioning
confidence: 99%
“…It was shown in another in vitro study that the extract of P. harmala has the ability to inhibit catechol-O-methyltransferase and thereby the methylation of catecholamines with a mixed type mechanism. [ 34 ] All of these effects represent an idea that P. harmala and its derivatives could be used for treatment of mood disorders and are potent alternatives for current anti-depression drugs.…”
Section: Effects On Nervous Systemmentioning
confidence: 99%
“…5,7a,12 Our results corroborate with the results of other studies that have also highlighted the inhibitory effects of several commercially available compounds. 11,13 Other studies have revealed that inhibition of methyltransferases has a significant effect on the dengue virus infection. 13,14 In order to validate the differences between eight different concentrations, we employed the ANOVA test.…”
Section: Effect Of Various Compounds On Mtase Activitymentioning
confidence: 99%
“…11,13 Other studies have revealed that inhibition of methyltransferases has a significant effect on the dengue virus infection. 13,14 In order to validate the differences between eight different concentrations, we employed the ANOVA test. Results of ANOVA showed statistically significant differences across eight different concentrations for both Azacitidine and Zebularine ( Figure 2B and 2C).…”
Section: Effect Of Various Compounds On Mtase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Several phytochemicals with catecholic structures have been studied for their inhibitory effects on COMT. Flavonols, isoflavones, catechins, alkaloids, and polyphenolic acids have been evaluated as COMT inhibitors and investigated for their implication in chemical-induced genotoxicity or their therapeutic value in treating Parkinson’s disease [ 16 , 17 , 18 , 19 ]. However, effects of phytochemicals belonging to the lignan class on COMT activity have not been reported yet.…”
Section: Introductionmentioning
confidence: 99%